2017
DOI: 10.1007/s00011-017-1077-8
|View full text |Cite
|
Sign up to set email alerts
|

Slc11a1 (Nramp-1) gene modulates immune-inflammation genes in macrophages during pristane-induced arthritis in mice

Abstract: Our data demonstrated the fine-tuning roles of Slc11a1 alleles modulating macrophage activation, and consequent PIA susceptibility, in those mouse lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…Seven genes were hypermethylated and 4 genes were hypomethylated. The hypermethylated genes have roles in asthma (VGLL4, AGR2) ( 24 , 28 ), neurologic development (AGAP1, OTX2) ( 29 , 30 ), and immune regulation (SCAMP5, SLC11A1) ( 31 , 32 ). The hypomethylated genes have roles in immune regulation (PPP4C) ( 27 ), transcription regulation (MIER2) ( 26 ), and inflammation (ABCC8) ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven genes were hypermethylated and 4 genes were hypomethylated. The hypermethylated genes have roles in asthma (VGLL4, AGR2) ( 24 , 28 ), neurologic development (AGAP1, OTX2) ( 29 , 30 ), and immune regulation (SCAMP5, SLC11A1) ( 31 , 32 ). The hypomethylated genes have roles in immune regulation (PPP4C) ( 27 ), transcription regulation (MIER2) ( 26 ), and inflammation (ABCC8) ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results with AIRmaxSS mice showed differential peritoneal macrophage gene expression profiles during PIA, with higher expression and production of H 2 O 2 , NO, IL-1b, IL-6, TNF-a, and several chemokines. The presence of the Slc11a1 R allele, on the other hand, diminished the intensity of macrophage activation, restricting arthritis development [ 16 ]. Pristane, hexadecane, squalene, and mineral oil also induce arthritis in Lewis and Dark Agouti rats.…”
Section: Discussionmentioning
confidence: 99%
“…In our linkage studies using AIRmax x AIRmin intercrosses, we mapped quantitative trait loci (QTL) for PIA susceptibility on chromosomes 5 and 8 that overlap QTL for experimental arthritis and other autoimmune diseases [ 2 ]. Gene expression profiling of paws from arthritic and nonarthritic AIRmax and AIRmin mice showed that among several differentially regulated genes, IL-1beta and CXC chemokines had higher expression in PIA-susceptible AIRmax mice, as well as in macrophages [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The unbalanced expression of the genes that promote osteoclastogenesis and inhibit osteoblast differentiation may represent a mechanism stimulating bone erosion and increasing disease severity in AIRmax animals. Histological analyses of the paws of the AIRmaxSS subline did, in fact, show bone loss in addition to the destruction of cartilage [42].…”
Section: Discussionmentioning
confidence: 99%